Induction of Biosynthesis Antioxidant Molecules in Young Barley Plants by Trioxygen - Natalia Matłok; Tomasz Piechowiak; Ireneusz Kapusta; Kamil Królikowski; Maciej Balawejder (Molecules, 2022)
Young barley plants are a good source of bioactive compounds. This paper presents the effects of gaseous O3 (trioxygen or ozone) on the biosynthesis of compounds, determining the antioxidant potential of young barley plants. The total content of polyphenols was determined along with their profile, as well as total antioxidant potential and vitamin C content. The highest contents of these compounds were identified in young barley plants exposed to gaseous O3. The main bioactive compound, representing polyphenols, determined in the examined raw materials was saponarin (isovitexin 7-O-glucoside). The induction of increased biosynthesis of these molecules was directly linked to the modification of the activity of selected enzymes. The increased polyphenol content resulted from the modified activities of polyphenol oxidase (PPO) and phenylalanine ammonia lyase (PAL). On the other hand, the oxidative effect of ozone on barley plants was reduced, owing to the modified activities of catalases (CAT), glutathione peroxidases (SOD) and guaiacol peroxidase (GPOX). Analysis of the results showed that by applying gaseous O3 at a dose of 50 ppm for 10 min, the contents of bioactive compounds can be maximised in a residue-free way by activating oxidative stress defence mechanisms.